Achalinus quangi, a new odd-scaled snake species from Vietnam - Pham, Anh Van; Pham, Cuong The; Le, Minh Duc; Ngo, Hanh Thi; Ong, An Vinh; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2023)
Based on morphological and molecular analyses, we herein describe a new species of Achalinus from northern Vietnam. Achalinus quangi sp. nov. differs from its sister taxon, A. emilyae, and other members of the genus Achalinus by at least 4% in terms of genetic divergence based on fragments of the mitochondrial COI and Cytb genes and a combination of the following morphological characters: (1) maxillary teeth 27–29; (2) suture between the internasals distinctly longer than that between the prefrontals; (3) loreal not fused with prefrontal, extending from the nasal to the eye; (4) supralabials six; (5) infralabials five; (6) postocular absent, temporals 2+2, only the upper one in broad contact with eye; (7) dorsal scales in 25(23)–23–23(21) rows, keeled; (8) ventrals 139–141 in males, 141–154 in females; (9) subcaudals 75–84 in males, 69 in the female, all unpaired; (10) cloacal entire; (11) dorsum reddish brown to brown. Achalinus quangi sp. nov. consists of two subclades, the first one occurring on the northern side of the Da River in Son La and Tuyen Quang provinces and another subclade found on the southern side in Thanh Hoa, Nghe An, and Ha Tinh provinces. These two subclades are separated from each other by 1.8 to 2.3% genetic divergence and are slightly differing in ventral scalation.